The lake house (New York Warner Books, 2004)
Out in the world for the first time since escaping horrifying government experiments, six children make their way toward the Lake House in the hope of being reunited with Kit and Frannie, a couple who once saved their lives.
Contains an excerpt from the author's Sam's letter to Jennifer (p. [383]-403).
Sequel to: When the wind blows.
Keywords: Flight -- Fiction; Genetic engineering -- Fiction; Human experimentation in medicine -- Fiction; Teenagers -- Fiction; Science fiction; Colorado -- Fiction; Washington (D.C.) -- Fiction; Mystery fiction; Science fiction; Suspense fiction; Science fiction; Suspense fiction